Attribution or non-attribution of the October 7 Hamas operations on Israel, to the Islamic Republic of Iran in the light of legal precedent and international instruments - Hossein Rezazadeh; Mohammad Abbasi Atoie (پژوهشنامه حقوق تطبیقی)
The Palestinian group Hamas launched military operations against Israel on October 7, 2023. Following this operation, some scholars believe that it can be attributed to the Islamic Republic of Iran. According to Article 8 of the Draft Articles on the Responsibility of States for Internationally Wrongful Acts (2001), the actions of a person or group of persons are attributed to a state if they are carried out on the instructions of, or under the direction or control of, that state. The main question that arises is what criteria are defined based on the threshold of guidance and control. According to international documents and judicial precedents, several criteria—including overall control, effective control, effective overall control, and ultimate control—are used to attribute a military group to a foreign state. Based on the principles of international law and any of the aforementioned criteria, the operations of October 7 are not attributable to the Islamic Republic of Iran. This research is descriptive-analytical and will be conducted in both Persian and English, utilizing library resources as well as electronic resources such as books, articles, theses, and official conference materials related to the topic, both regionally and internationally.